(untitled) (Revista de Ciências Agroveterinárias, 2018)
Several protocols to extract plant DNA exist, which can provide varying concentrations and quality of DNA due to the interaction between the protocol components and plant tissue compounds that affect the extraction, such as polyphenols and proteins. The objective of this study was to test the efficiency of different protocols for extracting DNA from apple tree leaves. Three DNA extraction protocols were tested: FastDNA® SPIN Kit - MP Biomedicals; adaptation from Qiagen DNeasy® Plant Mini Kit; adapted CTAB. Fresh and frozen young leaves of the genotypes M-10/09, SCS426 Venice and SCS427 Elenise were used. The purity and concentration of the DNA were analyzed using a spectrophotometer. The DNA extracted was tested using PCR with one primer related to regions of the genome that access transcription factors in apples (SAND). The highest concentrations of DNA were provided by the adapted CTAB protocol. Regarding purity, the adaptation from Qiagen DNeasy® Plant Mini Kit and the adapted CTAB protocols were considered satisfactory. Regarding DNA quality verified by PCR, all protocols were efficient for amplification of the target fragments. Therefore, all three protocols can be used for DNA extraction from apple leaves; however, the use of the adapted CTAB protocol showed high efficiency, due to the higher quality and concentration of DNA, with the lowest relative cost in the process of DNA extraction.